Antioxidant activity in children with ADHD – a comparison in untreated and treated subjects with normal children - Kukreja, Ruchi; Saxena, Anil Kumar; Gurtu, Sunil; Ali, Bashir; Sitholey, Prabhat (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2011)
Introduction: Attention deficit hyperactivity disorder (ADHD) is a frequently encountered clinical condition in children. Based on DSM IV-TR criteria it can be sub-classified into three distinct types namely hyperactiveimpulsive, inattentive and combined. Materials and Methods: In the present study, salivary antioxidant activity (AOA) in children with ADHD was compared with age-matched normal control subjects, both as a whole and also with regard to the three subtypes. Additionally, the effect of therapy on the altered AOA levels was investigated following short term (<3 months) and long term (1–3 years) treatments. AOA and catalase activities in the saliva were estimated employing previously reported biochemical procedures. Results: While AOA is decreased in ADHD patients as compared to normal subjects, statistically significant decrease is seen only in the combined and the hyperactive-impulsive subtypes. Restoration of AOA and catalase activities is seen only after sustained therapy and not in the short term. Conclusion: It is concluded that ADHD is associated with decrease in AOA and this should possibly also be addressed for limiting the long term outcomes of this condition.